Keratinized Gingiva Height Increases After Alveolar Corticotomy and Augmentation Bone Grafting. Issue 10 (1st October 2015) - Wilcko, M. Thomas; Ferguson, Donald J.; Makki, Laith; Wilcko, William M.
Abstract : Background: The aim of the present study is to compare the keratinized gingival tissue (KT) height labial to the mandibular incisors after active orthodontic treatment (AOT) with and without alveolar corticotomy and bone grafting. Methods: Two orthodontically treated groups of 35 patients each, with (Cort) and without (Conv) alveolar decortication and augmentation bone grafting, are matched in this case‐control study for sample size, sex, mandibular premolar extractions, pretreatment age, post‐treatment observation period, and pretreatment KT height. Standardized digital frontal occlusion photographs taken before and at least 1 year after AOT were adjusted to 96 dots per inch and measured with image analysis software for vertical KT height labial to each mandibular incisor. Results: An average of 1.5 years after completion of AOT, KT height had increased significantly by 0.78 mm ( P < 0.001) in the Cort group and decreased 0.38 mm ( P = 0.002) in the Conv group; a 1.28‐mm KT height gain was demonstrated in the subgroup representing the lowest half of Cort KT height at pretreatment. Mandibular incisor inclination and prominence explained neither the decrease in KT height in Conv nor the KT height gain in Cort. Conclusions: Orthodontic therapy combined with alveolar decortication and augmentation bone grafting resulted in a significant increase in KT height. Although KT height surrounding the dentition has been devalued by evidence‐based studies, the value‐added protection of KT height increase after decortication and augmentation bone grafting offsets the concerns of orthodontic proclination or expanding mandibular incisors facially.